Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Kombinasi Metode AHP dan PROMETHEE - Anzani, Siti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Employees are one of the most important assets for a company to be able to survive, develop, compete and earn profits. In an increasingly competitive business world, competition drives companies to work harder to improve their quality. And it takes maximum effort to improve employee performance. One of them is to choose the best employees in hopes of improving their performance. The difficulty in making decisions made by the HRD department in determining the best employees is due to the large amount of employee data and the selection process that still uses manual methods, causing a long processing time in decision making. Decision Support System selection of the best employees is carried out using the Analytical Hierarchy Process (AHP) method to determine the weight of the criteria, as well as the use of the Preference Ranking Organization Method Of Enrichment Evaluation (PROMETHEE) method to find the overall order/ranking. Based on the results of the process of applying the Analytical Hierarchy Process (AHP) method and Preference Ranking Organization Method Of Enrichment Evaluation (PROMETHEE) to determine the best employee performance evaluation goes to the employee with the name effendi with a score of 0.8426 where the value of each attendance criterion is 80%, “Very Good” skills, “Very Good” Teamwork, “Good” Discipline, “Good Enough” Ethics.